Fuzzy Linear Labeling - Mathew Varkey, T. K.; Sreena, T. D. (Asian Journal of Engineering and Applied Technology, 2019)
A fuzzy linear labeling of a graph is the existence of two injections which assigns values in [0,1]. This labeling fuzzifies the crisp graph. In this paper we show the admissibility of fuzzy linear labeling in some path related graphs.